Determination of the Nickel/Nickel Oxide Phase Transition and Henry's Constant in Hydrogenated Subcritical and Supercritical Water. Issue 1 (1st January 2015) - Moss, T.; Was, G. S.
Abstract : The objective of this study is to determine the temperature dependence of the nickel/nickel oxide phase transition using additions of dissolved hydrogen in subcritical and supercritical water. The dissolved hydrogen at the Ni/NiO boundary was measured by direct exposure of nickel coupons at 320 to 450°C and 25 MPa. The stable form of nickel at each exposure condition was determined by optical examination and confirmed by nuclear reaction analysis. Henry's law constant as a function of temperature was determined in-situ by measuring the fugacity of hydrogen through a palladium-silver tube using known dissolved hydrogen concentrations. Below 320°C, Henry's constant decreases linearly up to the critical temperature, above which the slope becomes temperature independent. The effect of water density on Henry's law constant was determined. A thermodynamic model for hydrogen fugacity at the Ni/NiO phase boundary was developed and was shown to agree with the measured data. The deviation in the fugacity at the critical temperature was accounted for by the inclusion of activity of water in the model, highlighting the importance of thermodynamic properties of solvents in high temperature oxidation.